2021
DOI: 10.1080/14725843.2021.1937051
|View full text |Cite
|
Sign up to set email alerts
|

Fisher migrations: social and economic perspectives on the emerging shark fishery in West Africa

Abstract: This paper explores the linkage between the expansion of commercial shark-fishing markets and the extension of migratory cycles of fishers in the West African Sub-region. The paper shows the societal deconstruction that occurred following the massive expansion of shark fishing over previous decades. It also points out that the approach of public decision makers and fisheries managers has contributed to the depletion of shark stocks, at the same time as contributing to a better appreciation of the current publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Nunoo et al [25] reported that the duration of sampling influences the abundance of species caught. For instance, [21] over a period of eleven (11) months recorded twenty-three (23) species of sharks from both the artisanal fisheries and trawlers compared to the current studies, which buttress the ascertain that sampling period affects the abundance of species.…”
Section: Species Abundancesupporting
confidence: 51%
See 1 more Smart Citation
“…Nunoo et al [25] reported that the duration of sampling influences the abundance of species caught. For instance, [21] over a period of eleven (11) months recorded twenty-three (23) species of sharks from both the artisanal fisheries and trawlers compared to the current studies, which buttress the ascertain that sampling period affects the abundance of species.…”
Section: Species Abundancesupporting
confidence: 51%
“…In Ghana, the shark fishery first developed around 1974 [10]. Shark fishing in West Africa has been undertaken as a commercial activity since the beginning of the 19th century, developed as a result of the growing demand for shark oil for lighting purposes [11]. Many fishers and traders generated between 80 and 100% of their income from shark fisheries [3].…”
Section: Introductionmentioning
confidence: 99%
“…This high level of pressure is likely a product of: (a) a lack of teleost fish due to prolonged exploitation and active industrial fisheries, including distant water fleets and IUU activity (Doherty et al, 2021; Sumaila et al, 2020) and (b) the role sharks and rays in local food security. Sharks and rays are a cheap source of protein, which also provide an extra source of income from selling sought after fins (Diop & Dossa, 2011; Sall et al, 2021). There are no historic data on species landed in the Republic of the Congo, but a recent report showed ~70% of interviewed fishers felt shark populations in Congolese waters has remained stable over time (Momballa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Migrant fishing is an integral part of the West African fisheries landscape (Failler et al, 2020;Sall et al, 2021). Its importance has increased since the 1980s with the motorisation of pirogues, the use of isothermal boxes, and the loading of ice for fish conservation (Failler, 2020;Dème et al, 2021c;Binet et al, 2012).…”
Section: Characterization Of the Migrant Fisherymentioning
confidence: 99%